If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + -14 = -17 Reorder the terms: -14 + N = -17 Solving -14 + N = -17 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + N = -17 + 14 Combine like terms: -14 + 14 = 0 0 + N = -17 + 14 N = -17 + 14 Combine like terms: -17 + 14 = -3 N = -3 Simplifying N = -3
| 5x^3+45x-20x^2-180=0 | | n*35=16 | | (8-4x)=15 | | 8+6x+x=64 | | 12x+30=18x+18 | | 9c^3-64=0 | | M=2p+3 | | -3d+9=3 | | 9x^2=38x-8 | | 5ln(5x+8)=30 | | -30=-15+b | | -x-8/2 | | t/6-6=15 | | 57y=7(8y-2) | | 6(y+8)-8y=35 | | 1.25*24=30 | | 3/4x=15(4/3) | | -7-1+x=-31 | | 25x*6x+12+16=23*10x | | 9m-22=68 | | 15x(14-2)= | | n*24=30 | | (4/3)3/4x=15(4/3) | | (2y-5)(7y-3)= | | 125-r=68 | | 3x^2+x-6=24 | | 14+3n=-2j+6 | | 15y=19y-7 | | 8q-38-11=29 | | a^2+b^2=89 | | 2c^3+14c-36c=0 | | -5(9-11x)+8x-10=9x-12 |